\documentclass{article} \input{macros} \input{commands} \begin{document} \begin{center}\large\bf CIS 570 --- Introduction to Formal Language Theory --- Fall 2006 \end{center} \begin{center}\Large\bf Exercise Set 1 \end{center} \begin{center}\large\bf Model Answers \end{center} \section*{Exercise 1} \renewcommand{\thesection}{ES1.1} \theoremnumber{1} We proceed by mathematical induction. \begin{description} \item[\quad(Basis Step)] We have that $3(0^2 + 0 + 2) = 3\ast 2 = 6 = 6\ast 1$ and $1\in\nats$. \item[\quad(Inductive Step)] Suppose $n\in\nats$, and assume the inductive hypothesis: \begin{displaymath} 3(n^2 + n + 2) = 6m, \eqtxt{for some} m\in\nats . \end{displaymath} We must show that, \begin{displaymath} 3((n+1)^2 + (n+1) + 2) = 6m, \eqtxt{for some} m\in\nats . \end{displaymath} We have that \begin{alignat*}{2} 3((n + 1)^2 + (n + 1) + 2) &= 3(n^2 + 2n + 1) + 3(n + 1) + 6 \\ &= 3n^2 + 6n + 3 + 3n + 3 + 6 \\ &= 3n^2 + 3n + 6 + 6n + 6 \\ &= 3(n^2 + n + 2) + 6(n + 1) \\ &= 6m + 6(n + 1) && \by{inductive hypothesis} \\ &= 6(m + n + 1) . \end{alignat*} Thus $3((n+1)^2 + (n+1) + 2) = 6(m + n + 1)$ and $m + n + 1\in\nats$. \end{description} \section*{Exercise 2} \renewcommand{\thesection}{ES1.2} \theoremnumber{1} We proceed by strong induction. Suppose $n\in\nats$, and assume the inductive hypothesis: for all $m\in\nats$, if $m